Citizenship as cultural flow: structure, agency and power - Mitra, Subrata Kumar (Springer, 2013)
The book addresses the very topical subject of citizen making. By delving into a range of sources - among them survey questions, historical documents, political theory, architectural design, and public policy - the book provides a unique analysis of when and why citizenship has taken root in India. Each chapter highlights the constant innovation of citizenship that has occurred in India's legal, political, social, economic and aesthetic arrangements as well as providing the basis for comparative analysis across South Asian cases and the European Union
Bearb. der früheren Aufl., erschienen u.d.T.: Citizenship and the flow of ideas in the era of globalization
Keywords: Geschichte; Indien; Bürgerschaft; Aufsatzsammlung; Staatsangehörigkeit; Bürgerrecht; Bürger